O PROCESSO DE PROJETO COLABORATIVO APOIADO POR MEIOS DIGITAIS SOB À ÓTICA DA CIBERNÉTICA - Ferrari, Fernanda Aparecida Marino; Chico, Lucas Edson de; Pratschke, Anja (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article proposes the use of a systemic organization method within a collaborative design process supported by a digital BIM platform. The systemic approach is based on the Viable System Model (VSM), developed by the English Management Cyberneticist Stafford Beer, which focuses on the organization of information and communication and its collaboration strategies during the different phases of a design process. The results presented are based on ongoing researches at the research group Nomads.usp, at University of São Paulo.